Penerapan Manajemen Organisasi Pelajar Pondok Modern Dalam Menanamkan Disiplin Santriwati - Ikrom, Moh. Ikrom Mubarok; Jamrizal, Jamrizal; Huda, Syamsul (Al-Miskawaih: Journal of Science Education, 2022)
The application of the holistic education system at Darussalam Gontor Modern Islamic Institution for girls Campus 7, comprehensively covers all aspects of female life. Including disciplinary education that is applied to all aspects of female student activities. This study aims to determine the application of management carried out by the management of the Student Organization of Pondok Modern (OPPM) related to the cultivation of discipline to female students. In this study, the author used a qualitative approach, which collected data using observation methods, interviews with speakers directly related to the topic of the title, and documentation. Results of the study: 1) The application of organizational management covering all aspects of POACE (Planning, Organizing, Actuating, Controlling, Evaluating) is the main factor in the success of organizational administrators in instilling student discipline at Darussalam Gontor Modern Islamic Institution for girls Campus 7. 2) The existence of inhibiting and supporting factors in the cultivation of discipline through the management of the Student Organization of Pondok Modern (OPPM). While the results of the cultivation of discipline, all cottage activities can run smoothly, the number of disciplinary violations committed by santriwati can be minimized, besides that from an academic point of view there is an increase in the value of preliminary test results by 5% from the previous year. Penerapan system pendidikan holistic yang ada di Pondok Modern Darussalam Gontor Putri Kampus 7 secara komprehensif mencakup seluruh aspek kehidupan santriwati. Termasuk pendidikan disiplin yang di terapkan kedalam seluruh aspek kegiatan santriwati. Penelitian ini bertujuan untuk mengetahui penerapan manajemen yang dilakukan oleh pengurus Organisasi Pelajar Pondok Modern (OPPM) terkait penanaman disiplin kepada santriwati. Dalam penelitian ini penulis menggunakan pendekatan kualitatif, yang pengumpulan data-datanya dengan metode observasi, wawancara dengan narasumber yang berkaitan langsung dengan topik judul, dan dokumentasi. Hasil dari penelitian ini: 1) Penerapan manajemen organisasi yang mencakup seluruh aspek POACE (Planning, Organizing, Actuating, Controlling, Evaluating) menjadi faktor utama kesuksesan para pengurus organisasi didalam menanamkan disiplin santriwati di Pondok Modern Darussalam Gontor Putri kampus 7. 2) Adanya faktor penghambat dan pendukung dalam penanaman disiplin melalui manajemen Organisasi Pelajar Pondok Modern (OPPM). Sedangkan hasil dari penanaman disiplin, seluruh kegiatan pondok dapat berjalan dengan lancar, jumlah pelanggaran disiplin yang dilakukan santriwati dapat diminimalisir, selain itu dari segi akademik adanya kenaikan nilai hasil muroja’ah 5% dari tahun sebelumnya.